Hepatitis C virus, alcoholic cirrhosis, and hepatocellular carcinoma - Goeser, Tobias; Müller, Hubert M.; Solbach, Christine; Töx, Ulrich; Kommerell, Burkhard; Theilmann, Lorenz (Cancer epidemiology, biomarkers & prevention, 1994)
We undertook a retrospective study to determine the prevalence of hepatitis C virus (HCV) and hepatitis B virus (HBV) infection in 81 Caucasian patients with confirmed hepatocellular carcinoma (HCC). Besides HBV and HCV serological markers, HCV RNA and HBV DNA were detected in serum and liver tissue by polymerase chain reaction. Overall, HCV RNA was found in 20 cases (25%), HBV DNA in 21 patients (26%), and coinfection in 3 patients (3%). HCV RNA in liver tissue was not found without virus in serum, whereas HBV DNA was found in the liver tissue of one patient without viremia. In an additional analysis, 32 patients with HCC and alcoholic cirrhosis (HCC-AC) were compared to 35 cases with AC without HCC and 35 cases with alcoholic hepatitis. The prevalence of HCV RNA in HCC-AC (19%) was significantly higher than in the other groups (AC, 3%; alcoholic hepatitis, 0%). HBV DNA was present in 19% of HCC-AC as compared to 3% of AC and 0% of alcoholic hepatitis. We conclude that the form of HCC in 50% of the patients in a Western European country is related to chronic viral hepatitis. Our data obtained from a group of patients having alcoholic liver disease with or without HCC suggest that the prevalence of HCV RNA or HBV DNA in these populations increases with the severity of hepatic injury.
Gesehen am 17.04.2025